"We're people of the snow:" Weather, climate change, and Inuit mental wellness. (October 2020) - Middleton, Jacqueline; Cunsolo, Ashlee; Jones-Bitton, Andria; Shiwak, Inez; Wood, Michele; Pollock, Nathaniel; Flowers, Charlie; Harper, Sherilee L.
Abstract: Rapid environmental change due to climate change impacts Inuit mental wellness by altering the relationships between people, place, livelihoods, and culture. Little is known, however, about how fluctuations in weather contribute to the experience of place and the connection to mental wellness in Inuit communities. This study aimed to characterize the importance of changes in weather among Inuit, and how these changes influence mental health and wellness in the context of climate change. Data were drawn from a community-driven and Inuit-led study in the Nunatsiavut region of Labrador, Canada. In-depth interviews (n = 116 people) were conducted between November 2012 to May 2013 in the five Nunatsiavut communities. Qualitative data were thematically analyzed using a constant comparative method. Results indicated that weather impacted mental wellness through three key pathways: 1) shaping daily lived experiences including connection to place and other determinants of wellbeing; 2) altering mood and emotion on a transient basis; and 3) seasonally influencing individual and community health and wellbeing. These results demonstrate the immediate role weather has in shaping mental wellness in Nunatsiavut. In turn, this understanding of the climate-mental wellness relationship points to multiple pathways for action on climate adaptation policy and programming, and underscores the need for more culturally-specific and place-based investigations to appropriately respond to the mental health impacts of climate change.